The spaces in-between: An appreciative inquiry into cross-boundary collaborative design for social innovations - Setton, Orli (Research of GSB, 2018)
In order to support Social Innovation, Social Designers advocate for the use of collaborative design methodologies, inclusive design processes, which produce innovative design outcomes and inclusive societies. While there is a large amount of literature on this topic from a European and US perspective, there is little understanding regarding the effect large social disparity between stakeholders has on these types of engagements. The researcher describes this as cross-boundary collaborative design for social innovation, where "boundary" refers to social and collective identity such as, gender, race, class, etc., which is a reality in most South African collaborative design engagements and a gap in the literature. Thus, this thesis explores this gap by asking the research question, what practices, mindsets and interpersonal interactions help to support effective cross-boundary collaborative design for Social Innovation? In order to answer this question, the researcher conducted 32 interviews followed by a single focus group with disparate stakeholders engaged in these types of initiatives. Using a Constructivist Grounded Theory approach and applying the lens of Appreciative Inquiry to her interview questions, she recorded narratives that focused on moments of effectiveness within these cross-boundary collaborative design engagements. What emerged from the data was a strong link between the quality of relationships between the disparate stakeholders and the effectiveness of the collaborative design process - what she described as "generative" relationships (connections built on trust, vulnerability, friendship and respect) that blurred the social boundaries between the participants and helped them move across the social divides with ease. This in turn increased the generative nature of the collaborative design process. Furthermore, these generative relationships were often established outside of the design process, in a preliminary phase (pre-project) before a design engagement began because this phase allowed the stakeholders to focus solely on building relationships, instead of generating design solutions. However, the importance of generative relationships does not feature strongly in the current collaborative design literature. Instead, it focuses mainly on developing communication methods as a way to support boundary crossing and views relationship building as a secondary by-product of a good communication method. This thesis, however, concludes that in order to support effective cross-boundary collaborative design engagements, this process should be flipped and attention be given to first building generative relationships that can then help to support the effectiveness of the cross-boundary communication methods and ultimately improve the over all crossboundary collaborative design process.